DEVELOPMENT OF TOURISM VILLAGE THROUGH CBT APPROACH IN KAYUTANGAN HERITAGE VILLAGE, MALANG CITY - Ribka Aprilia Murtikasari; Tukiman Tukiman (DIA: Jurnal Administrasi Publik, 2021)
Kayutangan Heritage Village is a tourism village that presents the authenticity of the village with all the historical relics in the form of buildings with Dutch colonial pattern, culinary, and socio-cultural people in it that become an attraction to be visited and enjoyed so as to bring up memories of the past. Kayutangan Heritage Village is managed and developed independently by The Tourism Conscious Group (Pokdarwis). This study aims to know, describe and analyze the Development of Tourism Villages through a Community Based Tourism (CBT) Approach in Kayutangan Heritage Village, Malang. The method used in this study is descriptive qualitative. Sampling techniques used are purposive sampling and snowball sampling. The results of this study show that Kayutangan Heritage Village has fulfilled all dimensions of CBT development, namely economic dimension, social dimension, cultural dimension, environmental dimension and political dimension as has been conveyed through the theory of CBT development dimension by Suansri quoted by Sunaryo (2013:142). However, the implementation of the development of Kayutangan Heritage Village through CBT has not been optimal, because there are some things that are still not considered in the economic and environmental dimensions.